Fault tolerance in WBAN applications - ElSalamouny, Malak Yousry (AUC Knowledge Fountain, 2018)
One of the most promising applications of IoT is Wireless Body Area Net-works (WBANs) in medical applications. They allow physiological signals monitoring of patients without the presence of nearby medical personnel. Furthermore, WBANs enable feedback action to be taken either periodically or event-based following the Networked Control Systems (NCSs) techniques. This thesis first presents the architecture of a fault tolerant WBAN. Sensors data are sent over two redundant paths to be processed, analyzed and monitored. The two main communication protocols utilized in this system are Low power Wi-Fi (IEEE 802.11n) and Long Term Evolution (LTE). Riverbed Modeler is used to study the system’s behavior. Simulation results are collected with 95% confidence analysis on 33 runs on different initial seeds. It is proven that the system is fully operational. It is then shown that the system can withstand interference and system’s performance is quantified. Results indicate that the system succeeds in meeting all required control criteria in the presence of two different interference models. The second contribution of this thesis is the design of an FPGA-based smart band for health monitoring applications in WBANs. This FPGA-based smart band has a softcore processor and its allocated SRAM block as well as auxiliary modules. A novel scheme for full initial configuration and Dynamic Partial Reconfiguration through the WLAN network is integrated into this design. Fault tolerance techniques are used to mitigate transient faults such as Single Event Upsets (SEUs) and Multiple Event Upsets (MEUs). The system is studied in a normal environment as well as in a harsh environment. System availability is then obtained using Markov Models and a case study is presented.